Resposta:
x = 1
Explicació:
ÉS FÀCIL!!
# -x ^ 2 + 2x-1 = 0 # { * COMPARAR AMB
# ax ^ 2 + bx + c #
nosaltres veiem
# a = -1, b = 2, c = -1 #
dividint el terme mitjà …. OBTENIM, PRODUCTE =#ca = -1 * -1 = 1 #
SUMA =
# 2# *
per tant
# -x ^ 2 + x + x-1 = 0 #
# -x (x-1) + (x-1) = 0
# (- x + 1) (x-1) = 0
d'aquí
x = 1 …………………………… esperem que ho obtingueu
* CHEERS !!: D *
Resposta:
# x = 1 #.
Explicació:
Aquesta equació es pot resoldre per factorització.
# -x ^ 2 + 2x - 1 = 0 #
# -1 (x ^ 2 -2x + 1) = 0
# x ^ 2 -2x + 1 = 0 #
# x ^ 2 - x - x + 1 = 0 #
#x (x-1) -1 (x-1) = 0 #
# (x-1) (x-1) = 0
Ara,
# x-1 = 0 #
Per tant, # x = 1 #.